(untitled) (Journal of Medicine, 2012)
Wilson’s disease (WD), also known as hepatolenticular degeneration, is an inborn error of metabolism inherited as an autosomal recessive trait, characterized by toxic accumulation of copper in the body, particularly liver, brain and eyes. In children,WD presents more often with hepatic manifestations like acute hepatitis,cirrhosis of liver or liver failure.We present an unusual presentation of WD in a 15 years old male child who presented with neuropsychiatric manifestations without hepatic involvement. DOI: http://dx.doi.org/10.3329/jom.v13i1.10086 JOM 2012; 13(1): 103-105